Inhibition of the skeletal muscle Lands cycle ameliorates weakness induced by physical inactivity - Justin L. Shahtout; Hiroaki Eshima; Patrick J. Ferrara; J. Alan Maschek; James E. Cox; Micah J. Drummond; Katsuhiko Funai (Wiley, 2024)
Abstract Background Lipid hydroperoxides (LOOH) have been implicated in skeletal muscle atrophy with age and disuse. Lysophosphatidylcholine acyltransferase 3 (LPCAT3), an enzyme of the Lands cycle, conjugates a polyunsaturated fatty acyl chain to a lysophospholipid to form a polyunsaturated fatty acid containing phospholipid (PUFA‐PL) molecule, providing substrates for LOOH propagation. Previous studies suggest that inhibition of the Lands cycle is an effective strategy to suppress LOOH. Mice with skeletal muscle‐specific tamoxifen‐inducible knockout of LPCAT3 (LPCAT3‐MKO) were utilized to determine if muscle‐specific attenuation of LOOH may alleviate muscle atrophy and weakness with disuse. Methods LPCAT3‐MKO and control mice underwent 7 days of sham or hindlimb unloading (HU model) to study muscle mass and force‐generating capacity. LOOH was assessed by quantifying 4‐hydroxynonenal (4‐HNE)‐conjugated peptides. Quantitative PCR and lipid mass spectrometry were used to validate LPCAT3 deletion. Results Seven days of HU was sufficient to induce muscle atrophy and weakness concomitant to a ~2‐fold increase in 4‐HNE (P = 0.0069). Deletion of LPCAT3 reversed HU‐induced increase in muscle 4‐HNE (P = 0.0256). No difference was found in body mass, body composition, or caloric intake between genotypes. The soleus (SOL) and plantaris (PLANT) muscles of the LPCAT3‐MKO mice experienced ~15% and ~40% less atrophy than controls, respectively. (P = 0.0011 and P = 0.0265). Type I and IIa SOL myofibers experienced a ~40% decrease in cross sectional area (CSA), which was attenuated to only 15% in the LPCAT3‐MKO mice (P = 0.0170 and P = 0.0411, respectively). Strikingly, SOL muscles were fully protected and extensor digitorum longus (EDL) muscles experienced a ~35% protection from HU‐induced reduction in force‐generating capacity in the LPCAT3‐MKO mice compared with controls (P < 0.0001 for both muscles). Conclusions Our findings demonstrate that attenuation of skeletal muscle lipid hydroperoxides is sufficient to restore its function, in particular a protection from reduction in muscle specific force. Our findings suggest muscle lipid peroxidation contributes to atrophy and weakness induced by disuse in mice.